2014
DOI: 10.1111/jcpt.12224
|View full text |Cite
|
Sign up to set email alerts
|

The Model for End-stage Liver Disease score is potentially a useful predictor of hyperkalemia occurrence among hospitalized angiotensin receptor blocker users

Abstract: The MELD score showed a stronger predictive performance for hyperkalemia than either serum creatinine or estimated glomerular filtration rate alone. Furthermore, the MELD score showed good predictive performance for ARB-related hyperkalemia among hospitalized patients. The clinical implications and reasons for these findings merit future investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…The physiopathologic association between the hyperkalemia and poor prognosis is complex and remains to be elucidated. The mechanisms that drive this poor prognosis are likely due to the occurrence of a severe disease and the use of therapeutic drugs, which in cases with a renal dysfunction may result in hyperkalemia [22]. This result is in line with our findings, indicating the positive relationship between serum potassium and creatinine as well as BUN, which are known markers of renal dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…The physiopathologic association between the hyperkalemia and poor prognosis is complex and remains to be elucidated. The mechanisms that drive this poor prognosis are likely due to the occurrence of a severe disease and the use of therapeutic drugs, which in cases with a renal dysfunction may result in hyperkalemia [22]. This result is in line with our findings, indicating the positive relationship between serum potassium and creatinine as well as BUN, which are known markers of renal dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that the Model for End-Stage Liver Disease (MELD) score, which is considered to be a marker of the severity of hepatic dysfunction, is a stronger predictor for angiotensin receptor blocker-related hyperkalemia than serum creatinine or eGFR alone, with MELD scores of ≥10 being associated with an increased risk of hyperkalemia [9].…”
Section: Discussionmentioning
confidence: 99%